2015
DOI: 10.1073/pnas.1504890112
|View full text |Cite
|
Sign up to set email alerts
|

Activation of peroxisome proliferator-activated receptor α stimulates ADAM10-mediated proteolysis of APP

Abstract: Amyloid precursor protein (APP) derivative β-amyloid (Aβ) plays an important role in the pathogenesis of Alzheimer's disease (AD). Sequential proteolysis of APP by β-secretase and γ-secretase generates Aβ. Conversely, the α-secretase "a disintegrin and metalloproteinase" 10 (ADAM10) cleaves APP within the eventual Aβ sequence and precludes Aβ generation. Therefore, up-regulation of ADAM10 represents a plausible therapeutic strategy to combat overproduction of neurotoxic Aβ. Peroxisome proliferator-activated re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
125
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 123 publications
(130 citation statements)
references
References 31 publications
5
125
0
Order By: Relevance
“…ChIP assays were performed using a kit (Millipore) as described earlier (21, 22). Briefly, after 3 h of stimulation, cells were fixed by adding formaldehyde, and cross-linked adducts were resuspended and sonicated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ChIP assays were performed using a kit (Millipore) as described earlier (21, 22). Briefly, after 3 h of stimulation, cells were fixed by adding formaldehyde, and cross-linked adducts were resuspended and sonicated.…”
Section: Methodsmentioning
confidence: 99%
“…For immunofluorescence staining (21, 22), rabbit polyclonal anti-TGFβ (1:100) and goat polyclonal anti-Iba1 (1:100) (Supplementary Table 1) were used. The samples were mounted and observed under an Olympus IX81 fluorescence microscope.…”
Section: Methodsmentioning
confidence: 99%
“…However, recently we have shown that PPARα also plays an important role in the modulation of synaptic function in hippocampus via transcriptional upregulation of CREB 68 . It has been also delineated that activation of PPARα in hippocampal neurons leads to the increase in ADAM10 transcription and subsequent non-amyloidogenic proteolysis of APP 9 . These reports highlight a lipid-independent role of PPARα in controlling brain function.…”
Section: Introductionmentioning
confidence: 99%
“…Although gemfibrozil, marketed as ‘Lopid’, is an agonist of PPARα and a FDA-approved drug for hyperlipidemia [23,24], it has been shown to have multiple beneficial effects [25-30]. The ability of gemfibrozil to cross blood-brain-barrier (BBB) has already been documented [31].…”
mentioning
confidence: 99%